easy. distribute everything first.
assuming the "." is a typo
-3x - 3 = 2x -16 + 3
-3x = 2x -10
5x = 10
x = 2
2006-11-13 10:49:04
·
answer #1
·
answered by polloloco.rb67 4
·
0⤊
0⤋
–3(x + 1) = 2(x – 8) + 3
distribute the -3 and the 2
-3x - 3 = 2x - 16 + 3
combine -16 and 3 and add 3x to both sides
-3 = 5x - 13
add 13 to both sides
10 = 5x
subtract both sides by 5
2 = x
ANSWER
x = 2
2006-11-13 18:58:00
·
answer #2
·
answered by trackstarr59 3
·
0⤊
0⤋
–3(x + 1) = 2(x – 8) + 3
-3x - 3 = 2x - 16 + 3
-3x - 3 = 2x - 13
-5x = -10
x = 2
2006-11-13 18:49:33
·
answer #3
·
answered by dizzawg16 3
·
0⤊
0⤋
-3(x + 1) = 2(x - 8) + 3
-3x - 3 = 2x - 16 + 3
-3x - 3 = 2x - 13
5x = 10
x = 2
Check:
-3(2 + 1) = 2(2 - 8) + 3
-3(3) = 2(-6) + 3
-3(3) = -12 + 3
-9 = -9
QED
2006-11-13 19:51:54
·
answer #4
·
answered by CSUFGrad2006 5
·
0⤊
0⤋
-3x-3=2x-16+3
-3x-3=2x-13
-3x=2x-10
-5x=-10
x=2
2006-11-13 18:52:30
·
answer #5
·
answered by Charlie 2
·
0⤊
0⤋
2 is the answer. See above
2006-11-13 19:09:30
·
answer #6
·
answered by tdbhc33 2
·
0⤊
0⤋